Populist foreign policy: the case of Italy - Giurlando, Philip (Canadian foreign policy journal, 2021)
The purpose of this paper is to answer the following four questions using Italy as a case study: (A) does populism represent, in the realm of foreign policy, a substantive rupture with its predecessors? (B) Are there differences between left-wing and right-wing populists in the realm of foreign affairs? (C) In what ways do domestic institutions constrain or enable populist action in the international arena? (D) Are international opportunities and constraints, especially ones which derive from a country's geopolitical position in the international system, an important determinant of populist foreign policy? General conclusions derived from the Italian case are that populist foreign policy does represent a substantive rupture with the international political orientations of traditional parties; that there are some differences between left-wing and right-wing populists in the realm of international affairs but that their similarities are more important; domestic institutions only partially constrain populists' foreign policy; and that structural international pressures are an important determinant of populist foreign policy. Another general conclusion is that populist governments among medium- or weaker-sized states use "soft balancing" as a tool of foreign policy.